Adaptive Mobile E-Learning Environment for Improving Educational Process - Ahmed A. Saleh; Hazem M. El-Bakry (Bulletin of Electrical Engineering and Informatics, 2013)
Over the last decade, the concept of e-learning has become an important topic. E-Learning today gives the student a central role in his/her own learning process. It allows students to try things out, participate in courses, tests and simulations like never before, and get more out of learning than before. On the other hand, mobile E-learning has many advantages that contribute in enhancing and facilitating the learning process. In this paper, an adaptive mobile E-Learning (AME-Learning) environment for logic gates, simplification of Boolean functions and related fields is presented. The presented model generates suitable courses for each student in a dynamic form. The proposed environment is designed by integrating visual basic, flash and other effective tools. The contributions of this paper are supporting AME-Learning environment to improve learning and an evaluation of its use in context.